"FUTURE PAST": TIME AND TELEOLOGY IN (ANCIENT) HISTORIOGRAPHY. Issue 3 (October 2014) - GRETHLEIN, JONAS
ABSTRACT The historian's account of the past is strongly shaped by the future of the events narrated. The telos, that is, the vantage point from which the past is envisaged, influences the selection of the material as well as its arrangement. Although the telos is past for historians and readers, it is future for historical agents. The term "future past, " coined by Reinhart Koselleck to highlight the fact that the future was seen differently before the Sattelzeit, also lends itself to capturing this asymmetry and elucidating its ramifications for the writing of history. The first part of the essay elaborates on the notion of "future past": besides considering its significance and pitfalls, I offset it against the perspectivity of historical knowledge and the concept of narrative "closure" (I). Then the works of two ancient historians, Polybius and Sallust, serve as test cases that illustrate the intricacies of "future past." Neither has received much credit for intellectual sophistication in scholarship, and yet the different narrative strategies Polybius and Sallust deploy reveal profound reflections on the temporal dynamics of writing history (II). Although the issue of "future past" is particularly pertinent to the strongly narrative historiography of antiquity, the controversy about the end of the Roman Republic demonstrates that it also applies to the works of modern historians (III). Finally, I will argue that "future past" alerts us to an aspect of how we relate to the past that is in danger of being obliterated in the current debate on "presence" and history. The past is present in customs, relics, and rituals, but the historiographical construction of the past is predicated on a complex hermeneutical operation that involves the choice of a telos. The concept of "future past" also differs from post‐structuralist theories through its emphasis on time. Retrospect calms the flow of time, but is unable to arrest it fully, as the openness of the past survives in the form of "future past" (IV).